Allergic rhinoconjunctivitis: pathophysiological mechanism and new therapeutic approach - Ciprandi, Giorgio; Leonardi, Salvatore; Zicari, Anna Maria; Tosca, Maria Angela; Marseglia, Gianluigi (Acta Biomedica Atenei Parmensis, 2020)
Allergic rhinoconjunctivitis (AR) is the most common IgE-mediated disease. A type2 immune response is involved in AR pathogenesis. Allergic inflammation is characterized by eosinophilic infiltrate and mediators release. AR treatment is usually based on medication prescription, including antihistamines and intranasal corticosteroids. However, medications may be prescribed for long periods and sometimes may be scarcely effective, thus aggressive strategy should be used. Therefore, complementary medicine is becoming attractive for patients at present. Nutraceuticals represent interesting therapeutic options in clinical practice. In this regard, a new compound has been designed containing Vitamin D3, Perilla extract, and quercetin.